Healthcare human resource development in Saudi Arabia: emerging challenges and opportunities-a critical review - Mohammed Khaled Al-Hanawi; Sami A. Khan; Hussein Mohammed Al-Borie (Frontiers Media S.A., 2019)
Abstract Background Saudi Arabia is currently passing through a transformational phase. There is a huge demand on the Saudi healthcare system to provide better healthcare facilities to the rapidly increasing Saudi population, as well as the growing elderly population. Lack of trained healthcare professionals and heavy reliance on foreign workers are significant aspects for policymakers to consider and deal with. It is also important to re-examine the healthcare Human Resource Development (HRD) initiatives so as to provide a huge reserve of healthcare professionals with appropriate learning and competence. Method This paper is a critical review based on secondary data collected from various sources including databases, reports, articles, books, government documents and earlier research undertaken in this regard. The paper is an attempt to document and evaluate the various steps suggested and undertaken by the new strategic plan, Vision 2030, and consequently documented in the National Transformation Program (NTP) adopted in April 2016 in the healthcare HRD sphere in Saudi Arabia. Results It has been shown that appropriate HRD capacity building needs to be adopted along with the aggressive policy regulation. It is also important to ensure that future health sector investment meets the needs of local healthcare HRD. Saudization and the adoption of the 'Nitaqat' program have played an effective role in pushing the Saudization targets in the private sector, and there is a huge scope for the absorption of young trained Saudi boys and girls in the healthcare sector. Conclusion Vision 2030 adopted in 2016 is a testimony to a revolutionary step undertaken by the government and that the healthcare sector is also passing through a major shift in its approach and execution. Vision 2030 has come out with a very clear sense of direction to the healthcare sector, and the projected shift from the existing one-third to two-third Saudi-to-foreigner workforce ratio by the year 2030 needs to be adopted carefully to turn the healthcare HRD challenges into opportunities.